Students seek public votes for best Ag Expo video - Uribes, Tom::::::::: (2013)
A Fresno State student-produced video touting the university's role in agriculture education is among 10 global finalists for the World Ag Expo 2014 video contest. Now the students seek public support to be chosen as the best.